STUDI KEANEKARAGAMAN JENIS BURUNG DI KAWASAN DANAU SANO NGGOANG KECAMATAN SANO NGGOANG KABUPATEN MANGGARAI BARAT NUSA TENGGARA TIMUR - Salci, Ursula Dewi; Masrilurrahman, LL. Suhirsan; Rachman, Irna Ningsi Amalia (Universitas Pendidikan Mandalika, 2024)
The Sano Nggoang Lake area is one of the areas that is the habitat of several types of birds, including endemic birds of Flores, namely the Flores Crow, Flores Kehicap, Flores Serindit, and Flores Celepuk. However, the existence of birds in the Sano Nggoang Lake area is not yet known with certainty the level of diversity. Therefore, it is necessary to conduct research on the diversity of bird species in an effort to conserve birds, especially endemic birds. The purpose of this study was to determine the diversity of bird species in the Sano Nggoang Lake area, Sano Nggoang District, West Manggarai Regency. This research was conducted in May 2022 in the Sano Nggoang Lake area. The method used in this study is the analysis method. The results of this study found 26 species of birds, namely: Grey-rumped Shama (Dicrurus leucophaes) 12, Black-naped Orioles (Oriolus chinensis) 9, White-rumped Eagles (Haliastur indus) 2, Flores Eagles (Spizaetus floris) 1, Honey-breasted Babar (Lichmera squamata) 11, Honey-birds (Cinnyris jugularis) 5, Flores Mouse Deer (Pachycephala nudigula) 4, Flores Parakeet (Loriculus flosculus) 2, Flores Scops-owl (Otus alfredi) 1, Flores Shrike (Monarcha sacendotum) 2, Flores Crows (Corvus florensis) 2, Branch-billed Shrikes (Hypothymis azurea) 10, Common White-eyes (Zosterops melanurus) 4, 5 Asian magpie robins (Terpsiphone paradise), 11 Sangihe magpie robins (Eutrichomyias rowleyi), 3 striped magpie robins (Turnix suscitator), 1 pale magpie robin (Cacomantis pallidus), 4 white-rumped kingfishers (Caridonax fulgidus), 1 sun oriole (Coracina), 5 mountain ducks (Anas superciliosa), 4 Timor tesia (Tesia everetti), 4 Flores fantails (Rhipidura diluta), 2 Wallacean magpie robins (Dicrurus densus), 2 horned magpie robins (Philemon buceroides), 2 emerald-billed magpie robins (Calchophaps indicha), 1 green junglefowl (Gallus varius). The highest level of bird diversity is (H’ = 0.2417) and the lowest level of diversity is (H’ = 0.0427), and the species diversity index (H’ = 2.9711) which is included in the medium level of diversity.